Penanganan depresi pada calon legislatif (caleg) gagal pasca pemilu 2024 - Hidayah, Chusnul Nurul; Ardani, Tristiadi Ardi (Maliki Interdisciplinary Journal, 2024)
Depression is one type of mental disorder that often occurs in the world. In 2024 in Indonesia, with elections, many failures experienced depression. This disruption can reduce positive energy, and make its sufferers drown in negative energy which make themfar from being happy. Depression can be called a normal response if an individual is experiencing an event that makes him depressed. However, it is considered a disorder or abnormal if it occurs outside the norm and has not healed within the time period when people usually recover. This article will explain several ways that can be done to deal with depression in failed legislative candidates. This research uses the library research method by comparing the findings and opinions of several authors of books or scientific works.